2009
DOI: 10.1111/j.1750-3841.2009.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allspice, Cinnamon, and Clove Bud Essential Oils in Edible Apple Films on Physical Properties and Antimicrobial Activities

Abstract: Essential oils (EOs) derived from plants are rich sources of volatile terpenoids and phenolic compounds. Such compounds have the potential to inactivate pathogenic bacteria on contact and in the vapor phase. Edible films made from fruits or vegetables containing EOs can be used commercially to protect food against contamination by pathogenic bacteria. EOs from cinnamon, allspice, and clove bud plants are compatible with the sensory characteristics of apple-based edible films. These films could extend product s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 36 publications
9
87
0
6
Order By: Relevance
“…Results showed that the addition of antioxidant agent and EOs to the coating solution increased their L*. In particular at day 0 and 1, there were significant differences in L* of apple slices coated with EOs or without EOs, similar to the results reported by Du et al (2009). A visible and significant decrease of lightness in fresh-cut apples during the storage at 0 °C was observed (Table 2).…”
Section: Colour Measurementssupporting
confidence: 78%
“…Results showed that the addition of antioxidant agent and EOs to the coating solution increased their L*. In particular at day 0 and 1, there were significant differences in L* of apple slices coated with EOs or without EOs, similar to the results reported by Du et al (2009). A visible and significant decrease of lightness in fresh-cut apples during the storage at 0 °C was observed (Table 2).…”
Section: Colour Measurementssupporting
confidence: 78%
“…Du et al [42] encontraram diferentes efeitos sobre alguns parâmetros de cor quando óleos essenciais de canela e cravo foram incluídos. A inclusão de óleo essencial de tomilho e o aumento de sua concentração incrementam levemente o matiz amarelo dos filmes sem alterar sensorialmente a aparência geral [6] .…”
Section: Efeito Da Adição Dos óLeos Essenciais Nas Propriedades Colorunclassified
“…Somente para os padrões vermelho (RSIN e RSEX) e verde por RSEX este comportamento foi oposto (Figura 4a e Figura 4b). Resultados similares foram obtidos por Du et al [42] e por Moradi et al [43] , em que o aumento da concentração de óleos essenciais de canela e extrato de uva diminuiu a luminosidade e a transparência dos filmes. Sanchez-González et al [44] , afirmaram que a inclusão de óleo essencial de tomilho diminuiu o brilho superficial pelo incremento da rugosidade e das irregularidades devido à migração do óleo à superfície.…”
Section: Efeito Da Adição Dos óLeos Essenciais Nas Propriedades Colorunclassified
“…Currently, plant EOs are being evaluated as alternative antibacterial treatments in fresh produce and their products. Many researchers have evaluated the antibacterial activities of EOs including lemon (Severino et al, 2014), cinnamon (Du et al, 2009;Knight and McKellar, 2007), clove (Du et al, 2009;Knight and McKellar, 2007), rosemary (Klancnik, 2009), oregano (Benavides et al, 2012;Gündüz et al, 2010), apricot (Friedman et al, 2004), Mentha piperita (Tyagi and Malik, 2011), persea (Joshi et al, 2010), Carum copticum (Hashemi et al, 2014) and Thymus vulgaris (Tsai et al, 2011), both in vitro and in food models such as fresh vegetables, fruit juices, etc. However, no studies have been conducted to evaluate the antibacterial effects of plant EOs (including star anise oil) in vegetable juice.…”
Section: Introductionmentioning
confidence: 99%